ENHANCEMENT OF GROWTH AND PRODUCTION OF GLYCINE MAX L. BY AMRUTJAL - Dr. ASHISH SINGH TOMAR, (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Amrutjal is used for the enhancement of plant growth and production of Glycine max L. (soybean). Glycine max L. (soybean) is leguminous crop of Fabaceae family. Soybean is a kharif crop sown in monsoon season to increase the growth and production of Glycine max L. Amutjal is used with different concentration with water 25%, 50%, 75%, and 100% and Water as control. Amrutjal is prepared by fresh cow dung 1 kg, cow urine 1 lit, jaggery 50 gm and it is dissolved in 10-liter water these are the basic ingredients for this product. All the materials were mixed in a plastic tub and kept undisturbed for 3 days to promote microbial multiplication. they are kept for 3 days undisturbed According to them, cow dung is a rich source of beneficial microorganisms and contains many bacteria. After 3 days, it is again mixed slowly by swirling hand/stick clockwise 12 times and anticlockwise 12 times. Stir slowly if you stir too violently then microbes may be killed. Stir by using wooden stick three times a day. This helps in distributing the microbes everywhere in the solution. From the second day onward the fermentation process is started from the fourth day microbial activities reaches we observed that the fermentation process starts on fourth day now Amrut Jal is ready to use. The six parameters of Glycine max L. are studied and results are calculated by statics method the parameters which are observed and calculated are 1. Plant height 2. Leaves no. of a Plant 3. Pod no. of a Plant 4. Seed no. in a Plant 5. Seed weight of ten seeds 6. Root length of plant is calculated. So due to microbial activity, minerals and enzyme present in AmrutJal the plant growth and production of Glycine max L. (Soybean) increases by increasing concentration of AmrutJal 25% then 50%, then 75%, then 100% AmrutJal respectively. All six parameters growth development and production increases respectively. AmrutJal is made up of cow urine, cow dung, black jaggary and water Cow urine is component of Amrut Jal it has 95% water, 2.5% urea, 2.5% minerals enzyme, salts and hormones, contains iron, carbonic acid, potash, nitrogen, ammonia, calcium, phosphorus, salts, manganese, Sulphur, phosphate, potassium, urea, uric acid, amino acids, enzymes, cytokines, lactose etc. these are the growth enhancer. And cow urine contain bacteria s like Bacillus mycoides, Enterococcus faecolis, Hafnia alvei, Paenibacillus pantothenticus, Escherichia coli, Proteus mirabilis, Staphylococcus epidermidis, Acimetobacter calcoacetius, and Erwinia rhapontic. Cow dung contain bacteria Bacillus and Clostridium which are spore forming and makes soil fertile mainly used as organic fertilizers. Jaggery used in AmrutJal is for fermentation process by which microorganism and bacteria growth and multiply rapidly water used as universal solvent. AmrutJal giving positive effect with increasing concentration and at 100% AmrutJal results were maximum due to bacteria, enzyme, minerals present in it. So by using AmrutJal we can get rid of chemical fertilizer, pesticide, weedicide and protect microorganism biodiversity which are beneficial for us and for environment.